New Zealand/Aotearoa - Sam, M. (Comparative elite sport development. Systems, structures and public policy, 2025)
New Zealand/Aotearoa (pop. 5 million) is a small state located in the South Pacific. Comprising two main islands, it enjoys a temperate climate, suitable for outdoor sports year-round. Like many states, sport has played an integral part in the development of its national identity (Jackson & Andrews, 1999). National pride has long been imbued in the country's iconic rugby team, the All Blacks but equally, since the 1960s and prior to any state involvement, New Zealand reputedly `punched above its weight` at the Olympic Games (Sam, 2015). Consequently, it was not until a series of disappointing performances in the late 1990s and early 2000s that elite sport came within the direct purview of government.